Pengenalan Warisan Budaya Melayu: Tepuk Tepung Tawar kepada Muda-Mudi Kelurahan Rejosari Kota Pekanbaru: Pengabdian - Jean Riani Agita; Dea Rahma Nur Graha; Ratu Ajeng Maharani Azzahra; Rista Egi Rifani; Rengganis Amanda Promesty; Nadia Rama Nila Sari; Selvi Yumanda; Muhammad Raziq Rabbani; Wildan Rafli Nugraha (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Indonesia is a country with abundant cultural, ethnic, and religious diversity. The Malay people, one of the thousands of ethnic groups inhabiting Indonesia, have traditions that are still preserved to this day, one of which is the Tepuk Tepung Tawar tradition. This tradition reflects the harmony between social, spiritual, and customary aspects, and serves as a social glue for the Malay community. Although originally derived from Hindu teachings aimed at asking for safety from the gods, this tradition has since interacted and blended with Islamic teachings, where ingredients such as bertih, white rice, and incense are now accompanied by the recitation of Shalawat and prayers. Amidst the currents of globalization and modernization, this tradition faces the challenge of a lack of understanding and involvement of the younger generation. Therefore, a socialization and direct practice of the Tepuk Tepung Tawar tradition was carried out in Rejosari Village, Pekanbaru, on June 25, 2025, targeting young people aged 13-19 years. The results of the socialization showed a significant increase in understanding, where all audiences were able to answer and understand the origins and implementation of the tradition after the direct practice. This underscores the importance of reintroducing this cultural heritage to ensure its continued success.